Demography and life history of a group of white‐bellied spider monkeys (Ateles belzebuth) in western Amazonia. Issue 8 (26th July 2018) - Link, Andrés; Milich, Krista; Di Fiore, Anthony
Abstract : Species‐specific demographic parameters and life history variables are important for understanding how individual primate taxa have adapted to evolutionary and ecological pressures and for conducting interspecific comparisons as well as for conducting population viability analyses and for managing captive populations. Here, we describe results from a 12+ year study of the demographic dynamics of a wild group of white‐bellied spider monkeys ( Ateles belzebuth belzebuth ) living near the Tiputini Biodiversity Station in a largely pristine rainforest in western Amazonia. Across the study period, group size varied between 25 and 37 individuals, and there was a clearly female‐biased sex ratio within all age classes. Females were the dispersing sex, as 19 females born into the group disappeared close to reaching adult body size and were presumed to have emigrated, while seven subadult or adult females joined the group during the study period. We estimated the age of dispersal for females at 5.9 ± SD 0.4 years ( N  = 13). Our study confirms that males are the philopatric sex, as all natal males have remained in the group and some have begun to reproduce, while no males have immigrated. Males began ranging independently from their mothers at ∼4.5 years of age and began copulating with adult females by the age of ∼5 years. Females had long inter‐birth intervals (44.2 ± SD 7.8 months; range: 32–64 months, N  = 21). Based on our data, female spider monkeys might have longer life spans than males, as only one out of six adult males but 9 out of 11 adult females present in the group in mid 2005 were still present in January 2018. The slow development and extended life histories of wild spider monkeys pose significant challenges for the ability of these primates to cope with habitat degradation and hunting throughout their geographical distribution. Abstract : Data from a long‐term study of 12+ years on wild spider monkeys confirm their slow development and long life cycles. Females are the dispersing sex in spider monkeys, and leave their natal groups around 6 years of age; males are philopatric and begin ranging independently from their mothers at ∼4.5 years of age and copulating with adult females by the age of ∼5 years. Given their long life history variables, spider monkeys face significant challenges under scenarios of habitat degradation and hunting.